ANALISIS PELAKSANAAN PEMBELAJARAN TATAP MUKA TERBATAS PADA PELAJARAN EKONOMI KELAS X SMAN 10 PONTIANAK - Ferga, Faris; Ulfah, Maria; Kuswanti, Heni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This thesis is titled "Examining the Constraints in Implementing Face-to-Face Learning for Economics Subjects in Class X SMA Negeri 10 Pontianak." The research focuses on the limitations encountered during the implementation of face-to-face learning. The objective of this study is to understand the extent of these limitations. The research methodology employed is the descriptive method, utilizing a qualitative approach to provide a detailed description. Various data collection techniques were employed, including direct communication with data collection tools, interview guidelines, direct observation with data collection tools, observation sheets, documentary studies with data collection tools, and data archives.    The planning phase of limited face-to-face learning has been successful. It is evident that teachers continue to plan the learning process by creating lesson plans, preparing teaching materials such as learning media, and arranging teaching materials prior to the commencement of the learning activities. The implementation of limited face-to-face learning has been executed effectively. This is evident from the adherence to health protocols during the limited face-to-face learning sessions.The evaluation of limited face-to-face learning implementation includes assessing student discipline in submitting assignments as a means of evaluation.